1993
DOI: 10.1002/1097-0142(19931001)72:7<2124::aid-cncr2820720711>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemoradiation in pancreatic and duodenal carcinoma. A phase II study

Abstract: Background. Low resectability rate and high locoregional recurrence are major factors contributing to the failure of surgical treatment for localized pancreatic adenocarcinoma. A Phase II study involving preoperative 5‐fluorouracil (5‐FU) and mitomycin C and radiation therapy was evaluated. Methods. Thirty‐one patients with biopsy‐proven carcinoma (24, head of pancreas; 2, body; 5 duodenum) were treated with preoperative radiation therapy, 5040 cGy (180 cGy/fraction, 5 days/week), concurrent with 5‐FU, 1000 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
0
6

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(65 citation statements)
references
References 21 publications
1
58
0
6
Order By: Relevance
“…Although the series is small, the results in terms of overall survival, symptomatic responses, the improvement or maintenance of a good PS as an indicator of quality of life and the generally low toxicity of therapy, suggests that there may be benefit of 5FU-based chemotherapy compared with palliative surgery alone (Sakker and Ware, 1973;Rotman et al, 1994). Various series or case reports have suggested that small bowel adenocarcinoma is a chemo-or radiosensitive disease, particularly in comparison with pancreatic cancer (Sakker and Ware, 1973;Jigyasu et al, 1984;Okhusa et al, 1991;Yeung et al, 1993;Coia et al, 1994). A series of fourteen patients, collected over a 30-year period and treated predominantly with 5-fluorouracil (5FU) containing regimens, reported one partial response (PR) lasting 12 weeks and 11 patients with minor responses or stable disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the series is small, the results in terms of overall survival, symptomatic responses, the improvement or maintenance of a good PS as an indicator of quality of life and the generally low toxicity of therapy, suggests that there may be benefit of 5FU-based chemotherapy compared with palliative surgery alone (Sakker and Ware, 1973;Rotman et al, 1994). Various series or case reports have suggested that small bowel adenocarcinoma is a chemo-or radiosensitive disease, particularly in comparison with pancreatic cancer (Sakker and Ware, 1973;Jigyasu et al, 1984;Okhusa et al, 1991;Yeung et al, 1993;Coia et al, 1994). A series of fourteen patients, collected over a 30-year period and treated predominantly with 5-fluorouracil (5FU) containing regimens, reported one partial response (PR) lasting 12 weeks and 11 patients with minor responses or stable disease.…”
Section: Discussionmentioning
confidence: 99%
“…The role of radiotherapy and chemotherapy is less clear. There are reports of prolonged survival with combination chemo-and radiotherapy following palliative bypass surgery or incomplete resection and reports suggesting a better prognosis compared with pancreatic carcinoma (Sakker and Ware, 1973;Yeung et al, 1993). Data on the use of chemotherapy alone are limited.…”
mentioning
confidence: 99%
“…[167][168][169] To date there have been no large randomised controlled trials of neoadjuvant therapy, so the evidence of its use remains entirely circumstantial. [170][171][172][173][174][175] These studies sometimes appear to provide spectacular results, but are often based on highly selected patients analysed using retrospective data collection and sub-group analyses. Snady et al reported a median survival of 23.6 months in 68 patients with locally invasive 'unresectable' pancreatic adenocarcinoma who had preoperative chemoradiotherapy (split-course radiotherapy plus 5-FU, streptozocin and CDDP), whilst 91 other patients who underwent a resection had a median survival of only 14 months.…”
Section: Adjuvant and Neo-adjuvant Chemoradiotherapymentioning
confidence: 99%
“…However, the impact of neoadjuvant therapy on survival is not clear. 55,56 Palliative treatment using radiation therapy with low-dose 5-FU as a radiosensitizer increased survival for patients with locally unresectable pancreatic cancer (Fig. 5).…”
Section: Chemotherapy and Radiation Therapymentioning
confidence: 99%